Revascularization Trends in Patients With Diabetes Mellitus and Multivessel Coronary Artery Disease Presenting With Non–ST Elevation Myocardial Infarction: Insights From the National Cardiovascular Data Registry Acute Coronary Treatment and Intervention Outcomes Network Registry–Get with the Guidelines (NCDR ACTION Registry–GWTG). (May 2016) - Pandey, Ambarish; McGuire, Darren K.; de Lemos, James A.; Das, Sandeep R.; Berry, Jarett D.; Brilakis, Emmanouil S.; Banerjee, Subhash; Marso, Steven P.; Barsness, Gregory W.; Simon, DaJuanicia N.; Roe, Matthew; Goyal, Abhinav; et al.
Abstract : Background—: Current guidelines recommend surgical revascularization (coronary artery bypass graft [CABG]) over percutaneous coronary intervention (PCI) in patients with diabetes mellitus and multivessel coronary artery disease. Few data are available describing revascularization patterns among these patients in the setting of non–ST-segment–elevation myocardial infarction. Methods and Results—: Using Acute Coronary Treatment and Intervention Outcomes Network Registry–Get with the Guidelines (ACTION Registry–GWTG), we compared the in-hospital use of different revascularization strategies (PCI versus CABG versus no revascularization) in diabetes mellitus patients with non–ST-segment–elevation myocardial infarction who had angiography, demonstrating multivessel coronary artery disease between July 2008 and December 2014. Factors associated with use of CABG versus PCI were identified using logistic multivariable regression analyses. A total of 29 769 patients from 539 hospitals were included in the study, of which 10 852 (36.4%) were treated with CABG, 13 760 (46.2%) were treated with PCI, and 5157 (17.3%) were treated without revascularization. The overall use of revascularization increased over the study period with an increase in the proportion undergoing PCI (45% to 48.9%; P trend =0.0002) and no change in the proportion undergoing CABG (36.1% to 34.7%; ptrend =0.88). There was significant variability between participating hospitals in the use of PCI and CABG (range: 22%–100%; 0%–78%, respectively; P value <0.0001 for both). Patient-level, but not hospital-level, characteristics were statistically associated with the use of PCI versus CABG, including anatomic severity of the disease, early treatment of adenosine diphosphate receptor antagonists at presentation, older age, female sex, and history of heart failure. Conclusions—: Among patients with diabetes mellitus and multivessel coronary artery disease presenting with non–ST-segment–elevation myocardial infarction, only one third undergo CABG during the index admission. Furthermore, the use of PCI, but not CABG, increased modestly over the past 6 years. Abstract : Supplemental Digital Content is available in the text.